2017
DOI: 10.3390/fib5010005
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Skeletal Muscle Fibres Promote Non-Muscle Stem Cells and Non-Stem Cells to Adopt Myogenic Characteristics

Abstract: Skeletal muscle fibres are unique cells in large animals, often composed of thousands of post-mitotic nuclei. Following skeletal muscle damage, resident stem cells, called satellite cells, commit to myogenic differentiation and migrate to carry out repair. Satellite stem cells migrate on muscle fibres through amoeboid movement, which relies on dynamic cell membrane extension and retraction (blebbing). It is not known whether blebbing is due to the intrinsic properties of satellite cells, or induced by features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Stem cells are known to interact and actively communicate with their surrounding microenvironment [23] via the secretion of cytokines and growth factors including but not limited to insulin-like growth factor-1 (IGF-1) [24], hepatocyte growth factor (HGF) [3], interleukins [25] and vascular endothelial growth factor (VEGF) [26]. These molecules regulate a variety of different cell activities essential in tissue regeneration, such as proliferation, angiogenesis and the modulation of inflammation [21, 27, 28].…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells are known to interact and actively communicate with their surrounding microenvironment [23] via the secretion of cytokines and growth factors including but not limited to insulin-like growth factor-1 (IGF-1) [24], hepatocyte growth factor (HGF) [3], interleukins [25] and vascular endothelial growth factor (VEGF) [26]. These molecules regulate a variety of different cell activities essential in tissue regeneration, such as proliferation, angiogenesis and the modulation of inflammation [21, 27, 28].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that seeding non-muscle stem cells onto the surface of muscle fibers induces them to adopt a SC mode of migration (Morash et al, 2017). More remarkable, we showed that adipose derived stem cells undergo a myogenic conversion following culture on the myofiber surface (Morash et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…The matrix governs the mechanisms by which cells migrate. For example, SC on their native substrate, the muscle fiber, move through an amoeboid-based mechanism, yet when the same cells are placed on plastic they develop lamellipodia (Morash et al, 2017;Otto et al, 2011) Surface matrix governs not only how cells migrate but ultimately can control what they become by regulating their fate. Engler and colleagues have elegantly demonstrated that hydrogel stiffness over two orders of magnitude directs fate decisions of human mesenchymal stem cells, and ultimately determines whether they form bone, muscle or neurons (Engler et al, 2006).…”
Section: Introductionmentioning
confidence: 99%